Dental caries prevalence, preventive behaviour and related factors among adolescents in Nigeria: a 10-year systematic review and meta-analysis - Adebukunola O. Afolabi; Adebola O. Ehizele; Ukachi Chiwendu Nnawuihe; Francisca O. Nwaokorie; Ucheoma Nwaozuru; Foluso Owotade; Joanne Lusher; George Uchenna Eleje; Omolola T. Alade; Folahanmi T. Akinsolu; Oliver C. Ezechi; Moréniké Oluwátóyìn Foláyan (BMC Oral Health)
Abstract Background The paucity of actionable data on the epidemiological profile of dental caries among adolescents in Nigeria poses significant challenges to policy formulation and implementation. This study aimed to estimate the prevalence of dental caries among adolescents in Nigeria and identify dental caries preventive behaviours associated with dental caries experience among adolescents in Nigeria over 10 years. Methods A systematic review and meta-analysis of studies on dental caries among adolescents was undertaken in September 2023. Literature searches were conducted across Academic Info, Cochrane Library, Refseek, and PubMed databases and Google Scholar, to identify studies on dental caries prevalence and dental caries preventive behaviour among adolescents in Nigeria that were published between January 2013 and December 2022. Eligible studies included cross-sectional, cohort, and case-control studies. Studies were also included if they presented data for at least one of the primary outcomes. Excluded were studies without information on the sample size, those with incomplete or overlapping samples, case reports, case series, editorials, or reviews without primary data. Heterogeneity was assessed using I2 percentages, and a funnel plot evaluated publication bias. A random effects model was used to determine the prevalence of dental caries with subgroup analysis by sex. The review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and the Joanna Briggs Institute (JBI) Critical Appraisal Checklist to assess the quality and integrity of the included studies. The systematic review was registered on PROSPERO (CRD42024458849). Results Sixteen studies met the eligibility criteria. The pooled prevalence of dental caries among adolescents in Nigeria was 23.0% (95% CI: 16–30). The pooled prevalence for males was 16.0% (95% CI: 9–23) and that for females was 22.0% (95% CI: 11–32). The commonest dental caries preventive practices reported were daily tooth brushing, use of fluoride-containing toothpastes, and dental service utilization. Factors associated with dental caries included a history of dental service utilization, poor oral hygiene practices, and consumption of refined carbohydrates in-between-meals. Conclusion The high prevalence of dental caries among adolescents in Nigeria warrants programmatic attention with an emphasis on improving oral hygiene practices and controlling the consumption of refined carbohydrates in-between-meals. Dental service utilization for dental caries preventive needs to be encouraged.